Navigating through hydrogen - Ben McWilliams; Georg Zachmann (Bruegel, 2021)
Hydrogen is seen as a means to decarbonise sectors with greenhouse gas emissions that are hard to reduce, as a medium for energy storage, and as a fallback in case halted fossil-fuel imports lead to energy shortages. Hydrogen is likely to play at least some role in the European Union's achievement by 2050 of a net-zero greenhouse gas emissions target. However, production of hydrogen in the EU is currently emissions intensive. Hydrogen supply could be decarbonised if produced via electrolysis based on electricity from renewable sources, or produced from natural gas with carbon, capture, and storage. The theoretical production potential of low-carbon hydrogen is virtually unlimited and production volumes will thus depend only on demand and supply cost. Estimates of final hydrogen demand in 2050 range from levels similar to today's in a low-demand scenario, to ten times today's level in a high-demand scenario. Hydrogen is used as either a chemical feedstock or an energy source. A base level of 2050 demand can be derived from looking at sectors that already consume hydrogen and others that are likely to adopt hydrogen. The use of hydrogen in many sectors has been demonstrated. Whether use will increase depends on the complex interplay between competing energy supplies, public policy, technological and systems innovation, and consumer preferences. Policymakers must address the need to displace carbon-intensive hydrogen with low-carbon hydrogen, and incentivise the uptake of hydrogen as a means to decarbonise sectors with hard-to-reduce emissions. Certain key principles can be followed without regret: driving down supply costs of low-carbon hydrogen production; accelerating initial deployment with public support to test the economic viability and enable learning; and continued strengthening of climate policies such as the EU emissions trading system to stimulate the growth of hydrogen-based solutions in the areas for which hydrogen is most suitable.
Keywords: 330